2019
DOI: 10.25139/ijair.v1i1.2029
|View full text |Cite
|
Sign up to set email alerts
|

Modified Vegenere Cipher to Enhance Data Security Using Monoalphabetic Cipher

Abstract: The rapid progression of exchange data by public networks is important, especially in information security. We need to keep our information safe from attackers or intruders. Furthermore, information security becomes needed for us. Many kind cipher methods of cryptography are improved to secure information such as monoalphabetic cipher and polyalphabetic cipher. Cryptography makes readable messages becoming non-readable messages. One of the popular algorithms of a polyalphabetic cipher is Vigenere cipher. Vigen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
2
0
1
Order By: Relevance
“…Because the encryption calculation only uses additive cipher, this algorithm is susceptible to attacks based on letter frequency analysis. The research's suggested approach entails combining the Vigenere encryption with a monoalphabetic cipher to increase its complexity [Kurniawan Muchamad(2019)]. A lot of introductory cryptology and computer security courses begin with or include a discussion of classical ciphers, which typically considers some cryptanalysis methods used to break them.…”
Section: Literature Surveymentioning
confidence: 99%
“…Because the encryption calculation only uses additive cipher, this algorithm is susceptible to attacks based on letter frequency analysis. The research's suggested approach entails combining the Vigenere encryption with a monoalphabetic cipher to increase its complexity [Kurniawan Muchamad(2019)]. A lot of introductory cryptology and computer security courses begin with or include a discussion of classical ciphers, which typically considers some cryptanalysis methods used to break them.…”
Section: Literature Surveymentioning
confidence: 99%
“…These ciphers are highly susceptible to a cryptanalysis attack [11]. However, there have been some recent enhancements [12,13] to these ciphers to overcome these attacks and to increase security and maintain performance. For example, Marzan and Sison [14] enhanced the key security of the Playfair Cipher Algorithm using a combination of a 16 × 16 matrix, XOR, two's complement, and bit swapping.…”
Section: Background and Related Workmentioning
confidence: 99%
“…Frobenius dan Hidayat yang memodifikasi algoritma Caesar, Vigenere, Hill dan Playfair yang dapat menyisipkan teks pada gambar tanpa mengubah ektensi[19]. Penelitian oleh Agustini dkk yang melakukan pengabungan onoalphabetic cipher dan Vigenere cipher dengan menerapkan key enkripsi sebanyak dua key[11]. Penelitian oleh Megantara dkk yang melakukan kombinasi algoritma Hill Cipher dengan LSB Cipher dalam mengamankan RGB image dengan proses membuat sistem penentuan pilihan panjang karakter pesan yang terdiri dari 32, 64 dan 128 karakter, yang kemudian dienkripsikan kembali oleh Hill Cipher[17].…”
unclassified